2019
DOI: 10.1093/icc/dtz034
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial dynamism and the built environment in the evolution of university entrepreneurial ecosystems

Abstract: University-centered entrepreneurial ecosystems (UCEEs) are complex webs of entrepreneurs, researchers, institutional support structures, and the built environment. We study the relationship between the built environment and the dynamism of the behavior of ecosystem agents in the evolution of UCEEs. Drawing upon data from interviews with ecosystem agents, as well as documents associated with the planning and development of purpose-built facilities (the built environment), we show how planned ecosystem evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
1
16
0
3
Order By: Relevance
“…These interdependencies have been discussed in other streams of the literature and at the city-level (Fritsch & Wyrwich, 2014;Levie & Autio, 2011) and are a crucial assumption in many other ecosystem studies that focus on other causal mechanism (e.g., Audretsch & Belitski, 2017, who link ecosystems to outputs). These co-evolutionary dynamics are the result of the interactions of individuals within ecosystems (Johnson et al, 2019;Thompson et al, 2018). The heterogeneity of ecosystem actors poses both a potentially fruitful but also challenging situation.…”
Section: Interdependence Of Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interdependencies have been discussed in other streams of the literature and at the city-level (Fritsch & Wyrwich, 2014;Levie & Autio, 2011) and are a crucial assumption in many other ecosystem studies that focus on other causal mechanism (e.g., Audretsch & Belitski, 2017, who link ecosystems to outputs). These co-evolutionary dynamics are the result of the interactions of individuals within ecosystems (Johnson et al, 2019;Thompson et al, 2018). The heterogeneity of ecosystem actors poses both a potentially fruitful but also challenging situation.…”
Section: Interdependence Of Elementsmentioning
confidence: 99%
“…The link between ecosystems and entrepreneurial activity in general, usually proxied by start-up rates, has been examined from different angles. These include how ecosystems support the university spin-offs (Harrison & Leitch, 2010;Johnson et al, 2019) as well as the interplay of government initiatives (Jung et al, 2017), institutions (Öner & Kunday, 2016), and human capital (Qian et al, 2013) with other ecosystem elements enables the formation of new ventures. Audretsch and Belitski (2017) showed that the ecosystem at the city-level with the addition of internet access and the integration of immigrants into the ecosystem fosters entrepreneurial activity.…”
Section: Outputsmentioning
confidence: 99%
“…The creation and evolution of an entrepreneurial ecosystem can be organically entrepreneur-led (Feld, 2012); alternatively and possibly simultaneously, it can be guided by the visible hand of government (Adams, 2020;Fuerlinger et al, 2015), or even anchored by large corporations Colombo et al, 2019;Ryan et al, 2020) and universities (Cunningham et al, 2019;Hayter, 2016;Johnson et al, 2019;Miller & Acs, 2017;Nicholls-Nixon et al, 2020). Additionally, an entrepreneurial ecosystem can mutate from a pre-existing system such as an industry cluster (Autio et al, 2018;Pitelis, 2012), or set of co-located clusters of varying vintages, through technological convergence in related and unrelated branches (Auerswald & Dani, 2017).…”
Section: An Evolutionary Perspective On Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…This might be a reflection of how most of the literature has dealt with the concept of EEs; the literature so far has been dominated by a static picture of EEs. Just recently, some have taken up a more evolutionary and dynamic perspective (Auerswald & Dani, 2017;Colombelli et al, 2019;Han et al, 2019;Johnson…”
Section: What Are Ees?mentioning
confidence: 99%